(untitled) - Costanzo, Francesco (New York, 2013)
Engineering Mechanics is also accompanied by McGraw-Hill's Connect which allows the professor to assign homework, quizzes, and tests easily and automatically grades and records the scores of the students' work
Keywords: Mechanics, Applied,Cơ học, Ứng dụng